Determinants of induced abortion among second-trimester pregnant women attending Dessie City health facilities, Northeast Ethiopia: a case-control study - Elsabeth Addisu; Bitya Admassu; Wolde Melese Ayele; Kassawmar Angaw; Bezawit Adane (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Globally, 10-15% of induced abortions occur in the second-trimester period, over half of which is considered unsafe, and disproportionately contribute to maternal deaths. However, there are limited information about determinants of induced abortion in second-trimester in the country, particularly in the study area. Therefore, this study aimed to identify determinants of induced abortion in the second-trimester.